Supporting the Effective Reintegration of Roma Returnees in the Western Balkans - World Bank Group (World Bank, Washington, DC, 2019)
The European Commission’s Directorate General for Neighborhood and Enlargement Negotiations approached the World Bank to develop an evidence base and to deliver policy advice and technical assistance for supporting the effective reintegration of (Roma) returnees in the Western Balkans: Albania, Bosnia and Herzegovina, the former Yugoslav Republic of Macedonia, Montenegro, Kosovo, and Serbia. This synthesis report presents the results of that research. This report documents the main socio-economic factors that drive migration from the Western Balkans to the EU. Returnees emphasize that they migrate to escape poverty, lack of housing, unemployment, the lack of or insufficient access to social security, and a consistent struggle and inability to provide a basic standard of living for themselves and their families. Poverty, discrimination, and historic marginalization reinforce one another and constitute strong push factors. Estimates suggest a substantial number of returnees belong to the Roma minority and that Roma are over-represented in migration and returnee flows. In addition, Roma and ethnic minorities have had to contend with systemic economic and social exclusion and institutional discrimination. Roma communities lack access to basic infrastructure and social services, are more likely to be underemployed, and have limited earning potential due to low incomes from unskilled jobs in the formal and informal sectors.